Combat-Related Hemipelvectomy: 14 Cases, a Review of the Literature and Lessons Learned. Issue 12 (December 2015) - D'Alleyrand, Jean-Claude G.; Lewandowski, Louis R.; Forsberg, Jonathan A.; Gordon, Wade T.; Fleming, Mark E.; Mullis, Brian H.; Andersen, Romney C.; Potter, Benjamin K.
Abstract : Objectives: Trauma-related hemipelvectomy is a rare and often fatal injury that poses a number of challenges to the treating surgeon. Our objective was to identify patient and injury characteristics that have proven difficult to treat, and to describe management techniques. Design: Retrospective review. Setting: Level II trauma center. Patients: Thirteen consecutive patients who underwent 14 combat-related hemipelvectomies between 2001 and 2013. Intervention: We reviewed our prospective trauma registry, along with the patients' medical records, radiographs, and clinical photographs. Main Outcome Measurements: Injury severity scores, required surgical procedures, ambulatory status, and bowel and bladder function. Results: Hemipelvectomy was indicated for insufficient soft tissue coverage, complicated by life-threatening local infection and/or a dysvascular hemipelvis. Five patients underwent resection for angioinvasive fungal infections. All patients sustained a genitourinary injury, with 7 requiring suprapubic catheters and all undergoing diverting colostomy. After a median of 2 years of follow-up, 2 patients had normal urinary continence and 3 regained fecal continence. The surviving patients required a mean of 44 operations. One patient returned to community ambulation. Conclusions: This is the largest published series of trauma-related hemipelvectomies. Our lessons learned may benefit civilian surgeons who are confronted with high-energy open injuries to the pelvic girdle. Although the decision to perform hemipelvectomy should not be taken lightly, this procedure can be lifesaving and should be performed in a timely fashion when indicated. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.